72 An educational initiative with the London academy of excellence tottenham (LAET) to provide 6th form students with an insight into nursing and medicine. An initiative by the GLA education team using videoconferencing. (23rd February 2023) - Broadhurst, Joanne; Simpson, Gabrielle; Cvetkovic, Mirjana
Abstract : Background: The LAET is an academically selective Free School for young people aged 16-19 years. It serves a multicultural & ethnically diverse community and seeks to break down the associated barriers students might face in securing a place at a top UK university and pursuing their desired career. Aims: To provide LAET students with an insight into the roles and responsibilities within Nursing and Medicine. To understand their experiences and perspectives and share the career opportunities at GOSH. Method: The session was facilitated via videoconferencing. A Nurse & Medic provided their career summaries and invited the students to respond. A SIM-at-a-distance session was then run. The mannequin and vital signs screen were shown in the videoconferencing window for the students to view. They were encouraged to ask questions and share their reflections. Results: Engagement: The students valued the opportunity to engage personally with the GLA Education Team and discuss possible careers in Nursing and Medicine. Aspiration and Motivation: The LEAT faculty commented that the GLA session helped the students link their current position studying for A-Level exams with their desired career. It broadened their scope regarding the career opportunities in healthcare. Collaboration: The students were impressed by the collaboration within the GLA Education Team. This led to clarification of the Nursing and Medical roles and the importance of interprofessional practice. Careers at GOSH: This overview was well-received by the students & highlighted GOSH as a World Class institution within their community. Conclusion: The GLA Education Team provided the LAET students with a unique insight into Nursing & Medicine. It enabled them to link their current educational pathway with a higher education pathway and possible career in Nursing or Medicine. It highlighted GOSH as a place of excellence, for both clinical care and community spirit.